Trimethoprim/sulfamethoxazole‐induced methemoglobinemia in pediatric patient: A case report - Sultan Alotaibi; Alaa Mously; Zainab Alnujaimy; Abdulansir Alotaibi; Abdullah Alharthi (Clinical Case Reports)
Abstract In this report, a case of high dose of sulfamethoxazole/trimethoprim‐induced methemoglobinemia and is reported in a young boy with ventilator‐associated pneumonia and was treated successfully with methylene blue and cessation of the offending agent.